2004
DOI: 10.1021/jp0477607
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Schemes in Ionic Liquid−H2O Systems:  A Thermodynamic Study

Abstract: We studied the hydration characteristics of room-temperature ionic liquids (IL). We experimentally determined the excess chemical potentials, , the excess partial molar enthalpies, , and the excess partial molar entropies in IL−H2O systems at 25 °C. The ionic liquids studied were 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim]BF4) and the iodide ([bmim]I). From these data, the excess (integral) molar enthalpy and entropy, and , and the IL−IL enthalpic interaction, , were calculated. Using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
220
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(238 citation statements)
references
References 31 publications
17
220
1
Order By: Relevance
“…A very similar behaviour of the solvatochromic shift of Reichardt's dye was obtained in case of [C 4 MIm][PF 6 ] addition to a water and ethanol mixture in the range of miscibility with the IL by Fletcher and Pandey [23]. In other work on binary IL/H 2 O mixtures [24], this was explained by salt dissolution at first and then hydration of ions at higher concentrations of IL. On dissolution of ILs into H 2 O at infinite dilution, IL ion pairs break away from their pure environment and settle in the water environment as hydrated ions.…”
Section: Resultssupporting
confidence: 67%
“…A very similar behaviour of the solvatochromic shift of Reichardt's dye was obtained in case of [C 4 MIm][PF 6 ] addition to a water and ethanol mixture in the range of miscibility with the IL by Fletcher and Pandey [23]. In other work on binary IL/H 2 O mixtures [24], this was explained by salt dissolution at first and then hydration of ions at higher concentrations of IL. On dissolution of ILs into H 2 O at infinite dilution, IL ion pairs break away from their pure environment and settle in the water environment as hydrated ions.…”
Section: Resultssupporting
confidence: 67%
“…1). Moreover, it has to be noticed that bulk solution behavior for water molecules around ions in both ILs (g i j (r) ≈ 1) can be observed at r ≥ The arrangement of the IL species can be studied throughG 22 . The values for EMIM/BF4 and BMIM/BF4 obtained by the direct and the inverse KB approach coincide and are largely negative, lying between ≈ −78 cm 3 /mol and ≈ −81 cm 3 /mol (EMIM/BF4) and ≈ −95 cm 3 /mol to ≈ −98 cm 3 /mol for BMIM/BF4.…”
Section: Mass Densities and Diffusion Coefficientsmentioning
confidence: 99%
“…As a prominent example, the influence of water significantly diminishes the broad electrochemical window known for pure ILs, 19 . In order to understand the profound hygroscopicity of ILs, several experiments and simulations were performed 9,13,17,[22][23][24][25][26][27] . An extensive discussion of the resulting effects can be found in recent reviews 16,28 .…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Based on thermodynamic parameters, such as excess chemical potentials and excess partial molar enthalpies and entropies, aggregations of 1-butyl-3-methlyimidazolium tetrafluoroborate (BMI + BF4 -) and BMI + iodide (BMI + I -) in aqueous solutions have been discussed. 6 This study revealed that the ILs form clusters in the range of IL mole fraction xIL > ~0. 5.…”
Section: Introductionmentioning
confidence: 99%